Serum uric acid, kidney function and acute ischemic stroke outcomes in elderly patients: a single-cohort, perspective study - Lorenzo Falsetti; William Capeci; Nicola Tarquinio; Giovanna Viticchi; Mauro Silvestrini; Vania Catozzo; Agnese Fioranelli; Laura Buratti; Francesco Pellegrini (Neurology International, 2017)
Chronic kidney disease and hyperuricemia have been associated to an increased risk and a worse prognosis in acute ischemic stroke. Several mechanisms, including platelet dysfunction, coagulation disorders, endothelial dysfunction, inflammation, and an increased risk of atrial fibrillation could be implicated. The role of serum uric acid in this setting is still object of debate. We enrolled all the consecutive patients admitted to our department for acute ischemic stroke. Cox regression analysis was used to evaluate the risk of in-hospital death considering serum uric acid levels and all the comorbidities. In the overall sample, hyperuricemia was independently associated to an increased risk of in-hospital mortality. This effect was stronger in patients with chronic kidney disease while, in the group of patients with normal renal function, the relationship between hyperuricemia and increased stroke mortality was not confirmed. Hyperuricemia could be associated to higher in-hospital mortality for ischemic stroke among elderly patients when affected by kidney disease. Survival does not seem to be affected by hyperuricemia in patients with normal kidney function.